The Social Media Influencers and Consumer Purchasing Intentions among Social Media Users - Gurung, Golman; Shah, Sonam Kumari; Gurung, Anu (Nepalese Journal of Business and Management Studies, 2023)
Social media influencer marketing encompasses the promotion of products or services involving product placement and endorsements from influencers. Influencers use their social media platforms to share videos, content, or images to shape consumers’ perceptions of various offerings. In this regard, this study examines how the trustworthiness and attractiveness of social media influencers influence consumers’ intentions to purchase different brands. The data were collected from 112 respondents residing in Tokha, Kathmandu, using a structured questionnaire distributed through convenient sampling. This research investigates the connection between influencers and consumer purchasing behaviour by employing descriptive, relational, and causal research designs. The results indicate a significant relationship between trustworthiness, attractiveness, and consumer purchasing intentions.